Mechanisms underlying the effects of cyanogenesis on development and reproduction of Tetranychus urticae: Insights from enzyme activity and gene expression aspects - Mufeng Wu; Xiao Liang; Ying Liu; Chunling Wu; Xingkui An; Zihua Zhao; Guifeng Hao; Ijiti Oluwole Gregory; Zhihong Li; Qing Chen (Ecotoxicology and Environmental Safety)
Cyanogenic plants can release toxic hydrogen cyanide (HCN) to defend against herbivory by hydrolyzing the cyanogenic glycosides (CNGs) with its β-glucosidases (β-GLUs). Numerous studies have speculated this CNG-mediated toxicity by a plant-pest interaction manner. However, the specific toxic effect of HCN was not well-demonstrated because of the interference of other ingested metabolites. Additionally, the physiological- and biochemical-based mode of action of HCN were seldom determined. To fill those knowledge gaps, the two-spotted spider mite (TSSM), Tetranychus urticae, was used as a model organism to elucidate the toxic mechanism of HCN. In addition, three CNG-enzyme combinations were screened for effective cyanogenesis and TSSM lethality. Linamarin-β-GLU (lima bean-derived) presented prompt HCN release, and molecular docking indicated higher binding energy and more robust binding sites compared with other two groups, i.e., lotaustralin-β-GLU (lima bean-derived) and amygdalin-β-GLU (almond-derived). Meanwhile, this combination led to higher TSSM mortality. Moreover, we found that the median lethal concentration of this combination will significantly prolong the developmental duration, and decrease the longevity and fecundity of TSSM. Besides, the population growth was also significantly suppressed. Furthermore, the sustainable activation of enzyme activity and the encoding gene expression related to physiological process such as detoxification (cytochrome P450, glutathione S-transferase, UDP-glucuronosyltransferase and β-cyanoalanine synthase), antioxidation (superoxide dismutase, catalase and peroxidase), neural transduction (acetylcholinesterase) and respiration (cytochrome c oxidase) were attributed to the detrimental impact on development and reproduction of TSSM. The present findings can provide insight regarding reasonable utilization of toxic chemicals in pest management and creation of novel pest-resistant germplasm.